Quality of care for severe acute malnutrition delivered by community health workers in southern Bangladesh. Issue 1 (20th April 2012) - Puett, Chloe; Coates, Jennifer; Alderman, Harold; Sadler, Kate
Abstract This study assessed the quality of care provided by community health workers (CHWs) in managing cases of severe acute malnutrition (SAM) according to a treatment algorithm. A mixed methods approach was employed to provide perspectives on different aspects of quality of care, including technical competence and acceptability to caretakers. CHWs screened children at community level using a mid‐upper arm circumference measurement, and treated cases without medical complications. Fifty‐five case management observations were conducted using a quality of care checklist, with 89.1% (95% confidence interval: 77.8–95.9%) of CHWs achieving 90% error‐free case management or higher. Caretakers perceived CHWs' services as acceptable and valuable, with doorstep delivery of services promoting early presentation in this remote area of Bangladesh. Integration of the treatment of SAM into community‐based health and nutrition programs appears to be feasible and effective. In this setting, well‐trained and supervised CHWs were able to effectively manage cases of SAM. These findings suggest the feasibility of further decentralization of treatment from current delivery models for community‐based management of acute malnutrition.